Academic performance of students in an education faculty of a public university in Lima and their perception of academic quality of teachers - Torres valladares, Manuel (2007)
The study was developed in a faculty of education of a public university of Lima, on a sample of 260 students pertaining to the first year of studies. In this investigation study the correlations that could exist between the academic yield of the students and the perception who these have of the academic quality of their educational ones, for it I am used an instrument to evaluate the quality of the teachers and the notes that the students obtained during the first academic year. The results of the psicométrico analysis, demonstrated to the validity of constructo and the trustworthiness of the Inventory of Educational quality. The analysis of the results indicated that, basically, significant correlations between both variables do not exist, except for which can be considered like losses. The comparative analysis by sort indicated that significant differences with respect to the educational quality do not exist, but however if they exist in the academic yield, noticing that women present/display values higher than men. In which one talks about to the comparisons by specialty, one was that significant differences in all the areas with the exception of the scale exist to know how to do.